Low-complexity turbo product code for high-speed fiber-optic systems based on expurgated BCH Co- des - Paludi, Franco; Morero, Damian A.; Goette, Teodoro A.; Schnidrig, Matias S.; Ramos, Facundo A.; Hueda, Mario R. (2024)
Fil: Paludi, Franco. ClariPhy Argentina S.A; Argentina.